038 Differences in the Gut Microbiome Composition Between Men with Peyronie's Disease and a Matched Cohort: A Pilot Study. (1st May 2022) - Osman, M.M.; El-Khatib, F.M.; Dianatnejad, S.; Nguyen, J.; Choi, E.; Towe, M.; Yafi, F.A.
ABSTRACT: Introduction: There have been no studies to-date that have attempted to establish an association between the gut microbiome (GM) and Peyronie's disease (PD). There are numerous inflammatory diseases that are associated with both the GM and PD, making an association between the two highly likely. Objective: To analyze stool samples from patients with PD and compare them to matched controls for differences in their GM. Methods: We collected stool samples from 27 patients with PD and 41 control. All samples were processed by a third-party company, Viome Inc. The samples were analyzed by metatranscriptome sequencing which allows for data to show both the taxonomy of the microbiome and its KEGG orthology (KO). KO is defined as the current molecular functions and pathways that are occurring in the GM. We compared richness and prevalence of the taxa and KOs between the PD and control groups. Results: 1, 477 taxa and 4, 762 KOs were detected in the 68 samples. The Mann-Whitney non-parametric test showed that the richness of both the taxa and KOs were non-significantly higher in the control samples (p=0.1168 and p=0.1672), respectively. One taxon, Massilioclostridium coli, was found to be significantly higher in the control group (adjusted Benjamini-Hochberg p-value=0.044). There were, however, no significant differences in prevalence of KOs between the two groups. Conclusions: This is the first study to look at associations between the GM and PD. We found a non-significant higher richness for both taxa and KOs in the control group. One taxon, Massilioclostridium coli, was present in significantly higher proportion in the control group (p=0.044). The clinical relevance of this finding is yet to be elucidated. Disclosure: Work supported by industry: yes, by Viome Inc.. A consultant, employee (part time or full time) or shareholder is among the authors (Antares. Clarus. Coloplast. Promescent.).